Asymmetric total synthesis of eicosanoid - Mohapatra, Debendra K.; Yellol, G. S. (Arkivoc, 2005)
An asymmetric total synthesis of eicosanoid 4 starting from 2,2- dimethyl-( R)- 1,3- dioxolane-4- carbaldehyde is described. The key steps involved for the synthesis include modified Simmons-Smith cyclopropanation, stereoselective reduction, ring-closing metathesis (RCM) and Nozaki- Hiyama- Kishi coupling reaction.
Keywords: cyclopropanation; eicosanoid; lipoxygenase inhibitors; Ring-closing metathesis; Stereoselective

Novel process for the synthesis of class I antiarrhythmic agent (+/-)-cibenzoline and its analogs - Gholap, Atul R.; Paul, Vincent; Srinivasan, Kumar V. (Synthetic Communications, 2008)
Synthesis of (+/-)-cibenzoline and its analogs has been achieved by a simple sequence of reactions. The diaryl cyanoolefin intermediate 3 could be prepared by Knoevenagel condensation of benzophenone with ethylcyanoacetate to form the tetra-substituted olefin intermediate 2 followed by Krapcho deethoxycarbonylation or from beta-hydroxynitrile intermediate 2' followed by the elimination of hydroxyl group respectively. The 2,2-diphenylcyclopropanecarbonitrile 4 was synthesized from intermediate 3 by cyclopropanation, which was converted to (+/-)-2-(2,2-diphenylcyclopropyl)-2-imidazoline 5 by reaction with ethylenediamine in the presence of a catalytic amount of sulfur. Moreover, the obtained 2-imidazolines were smoothly oxidized to the corresponding imidazoles 6 in good to moderate yields.
Keywords: Benzophenone; cibenzoline; cyclopropanation; diaryl cyanoolefin

Total synthesis of (-)-nardoaristolone B - Ople, Rohini S.; Handore, Kishor L.; Kamat, Nidhi S.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2016)
A stereoselective total synthesis of (-)-Nardoaristolone B, a nor-aristolane sesquiterpenoid natural product with an unusual 3/5/6 tricyclic ring system is described. The highlights of the present work includes use of (+)-(R)-Pulegone as a chiral-pool starting material, ring-closing metathesis, allylic oxidation and stereoselective cyclopropanation. In addition, a new analogue of Nardoaristolone B (minor product from the final step) was isolated in pure form and fully characterized with the help of single-crystal X-ray analysis.
Keywords: Chiral pool; cyclopropanation; Nardoaristolone B; Natural products; Total synthesis